2022
DOI: 10.3390/ijms231810881
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Pharmacology of COVID-19 mRNA Vaccines: Playing Dice with the Spike?

Abstract: Coronavirus disease-19 (COVID-19) mRNA vaccines are the mainstays of mass vaccination campaigns in most Western countries. However, the emergency conditions in which their development took place made it impossible to fully characterize their effects and mechanism of action. Here, we summarize and discuss available evidence indicating that COVID-19 mRNA vaccines better reflect pharmaceutical drugs than conventional vaccines, as they do not contain antigens but an active SARS-CoV-2 S protein mRNA, representing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 74 publications
0
38
0
Order By: Relevance
“…As one might expect, discrepancies in the nature of post-vaccination AEs may reflect, in addition to batchto-batch variations, a differential tissue/organ distribution of the vaccine formulation upon injection, whereas differences in the intensity of the symptoms may relate to the unknown, but presumably high level of spike protein produced by the cells, which are forced to express, against their nature, a biologically active but synthetic viral protein. Indeed, in a woman with mRNA-1273 COVID-19 vaccine-induced thrombocytopenia, plasma spike (S) protein level 10 days after vaccination was 10 ng/ml (Appelbaum et al, 2022), nearly 100 times higher than those reported by Ogata and colleagues in vaccinated subjects with no apparent adverse effects (Ogata et al, 2022), pointing to excessive vaccine-induced production of spike protein possibly causing AEs (Cosentino & Marino, 2022a, 2022b. The uncertainty surrounding the dose of the active product administered, which may be highly variable, and its biodistribution is deemed to be sufficient to justify a conscientious objection to mRNA technology (Provost et al, 2022).…”
Section: Mechanisms Underlying Aesmentioning
confidence: 78%
“…As one might expect, discrepancies in the nature of post-vaccination AEs may reflect, in addition to batchto-batch variations, a differential tissue/organ distribution of the vaccine formulation upon injection, whereas differences in the intensity of the symptoms may relate to the unknown, but presumably high level of spike protein produced by the cells, which are forced to express, against their nature, a biologically active but synthetic viral protein. Indeed, in a woman with mRNA-1273 COVID-19 vaccine-induced thrombocytopenia, plasma spike (S) protein level 10 days after vaccination was 10 ng/ml (Appelbaum et al, 2022), nearly 100 times higher than those reported by Ogata and colleagues in vaccinated subjects with no apparent adverse effects (Ogata et al, 2022), pointing to excessive vaccine-induced production of spike protein possibly causing AEs (Cosentino & Marino, 2022a, 2022b. The uncertainty surrounding the dose of the active product administered, which may be highly variable, and its biodistribution is deemed to be sufficient to justify a conscientious objection to mRNA technology (Provost et al, 2022).…”
Section: Mechanisms Underlying Aesmentioning
confidence: 78%
“…The emergence of SARS-CoV-2 prompted a global effort to develop protective vaccines. mRNA is an attractive form of the vaccine due to the exibility in antigen design and development and production [47][48][49][50][51] . However, effective mRNA vaccines require e cient delivery to cells and high antigen expression levels to induce robust immune responses and long-lasting protective immunity [52] .…”
Section: Discussionmentioning
confidence: 99%
“…This evidence raises the question as to whether it is correct to consider any adverse events of the COVID-19 vaccination exclusively within 14–21 days after inoculation, given that the inoculated products persist for longer. Cosentino M. et al discuss that mRNA vaccines must be considered to be pharmaceuticals, and their pharmacokinetics should be studied in greater detail [ 124 ]. Both mRNA and Spike have been found in the breast milk of vaccinated women, which demonstrates that these products travel into the body and can be excreted with biological fluids [ 125 ].…”
Section: Possible Mechanisms Of Covid-19 Mrna Vaccine-induced Tissue/...mentioning
confidence: 99%